Kecerdasan Spiritual Dalam Menghindari Perilaku Menyimpang Pada Siswa Kelas VIII SMP Negeri 1 Surakarta Tahun Pelajaran 2014/2015 - Marsini, Marsini, Dr. Badaruddin, M.Ag, Drs. M. Darojat Ariyanto, M.Ag (2015)
Spiritual intelligence can make a smarter spiritually religious. If a person has a spiritual intelligence then it is likely to have the ability to avoid deviant behavior. The purpose of this study was to describe the spiritual intelligence to avoid aberrant behavior in class VIII SMP Negeri 1 Surakarta in 2014/2015 academic year. The method used is qualitative research, data collection techniques with documentation and interviews and data analysis technique is used qualitative descriptive analysis, inductively implemented starting from data collection, data reduction, data presentation, and data verification. The results showed that the spiritual intelligence to give color to avoid misconduct proven to students of SMP Negeri 1 Surakarta has a high spiritual intelligence to avoid misbehavior. They have the character of a religious, honest, tolerant, hard working, creative, independent, democratize, curiosity, the spirit of nationalism, patriotism Air, cherish the achievements, friendly and communicative, love peace, love reading, environmental care, social care and responsibility responsibility. Supporting factor is the family environment and a good community, while the inhibiting factor is the awareness of students to avoid deviant behavior are external factors, coming from poor environmental and internal factors coming from within the students themselves.